Bagaimana cara berpikir desainer (How designers think) Bryan Lawson; penerjemah, Harfiyah Widiawati; editor, Alfatri Adlin - LAWSON, Bryan; Widiawati, Harfiyah; Adlin, Alfatri (2007)
XLviii, 316 hlm ilus 21 cm